Aerodynamics and Stability of the Flow in Relatively Long Cyclone Chambers - E. N. Saburov; D. A. Onokhin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
The article presents and analyzes the results of an experimental study of the aerodynamics of the flow in the working volume of cyclone chambers of a large relative length, significantly exceeding the length of the chambers that were used in the previous studies. Air supply to the chamber swirler was carried out tangentially from diametrically opposite sides by two inlet channels. The air discharge from the working volume of the chamber was made from the opposite end of the chamber through a round axisymmetric hole. The values of the area of the inlet channels and the diameter of the outlet were varied with replaceable incrustations and clamps. The experiments were performed with the use of laser Doppler anemometry. As a result, previously unknown features of flow formation in the working volume of relatively long cyclone chambers have been determined. The main characteristic values of the working volume flow have determined as well. In particular, the determining influence of the flow core characteristics on its structure in relatively long cyclone chambers has been discovered. The calculated ratios have been chosen to determine these values depending on the geometrical characteristics of the chamber under study. The boundary of the near-wall flow region, in which favorable conditions for the flow instability are created, is determined. Numerical simulation of the flow in the ANSYS Fluent software has been performed. Based on its results, a comparison of the results of numerical simulation, calculated dependencies and experimental data is presented. A comparison of the results demonstrated a completely satisfactory coincidence. Data obtained in the process of research and calculated ratios can be used in engineering practice and are of an interest from the point of view of further study of aerodynamics in a highly swirled flow of cyclone devices in order of to improving the methods of their thermal and aerodynamic calculations.